2011
DOI: 10.1152/ajpregu.00437.2010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mitochondrial morphology and function by O-GlcNAcylation in neonatal cardiac myocytes

Abstract: Mitochondria are crucial organelles in cell life serving as a source of energy production and as regulators of Ca(2+) homeostasis, apoptosis, and development. Mitochondria frequently change their shape by fusion and fission, and recent research on these morphological dynamics of mitochondria has highlighted their role in normal cell physiology and disease. In this study, we investigated the effect of high glucose on mitochondrial dynamics in neonatal cardiac myocytes (NCMs). High-glucose treatment of NCMs sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 49 publications
5
81
0
Order By: Relevance
“…Indeed, exposure of cardiac myocytes to high glucose increases mitochondrial protein O-GlcNAcylation; impairs the activity of complex I, III, and IV; and lowers cellular ATP and mitochondrial calcium content (21). High glucose also increases mitochondrial fragmentation and decreases mitochondrial membrane potential (48). Furthermore, a recent study revealed that the levels of OGT and OGA are dramatically altered in mitochondria from diabetic mice hearts with significant mislocalization of OGT in the mitochondrial matrix and reduced interaction of OGT with complex IV (22).…”
Section: Spotmentioning
confidence: 99%
“…Indeed, exposure of cardiac myocytes to high glucose increases mitochondrial protein O-GlcNAcylation; impairs the activity of complex I, III, and IV; and lowers cellular ATP and mitochondrial calcium content (21). High glucose also increases mitochondrial fragmentation and decreases mitochondrial membrane potential (48). Furthermore, a recent study revealed that the levels of OGT and OGA are dramatically altered in mitochondria from diabetic mice hearts with significant mislocalization of OGT in the mitochondrial matrix and reduced interaction of OGT with complex IV (22).…”
Section: Spotmentioning
confidence: 99%
“…The overexpression of OPA1 may be a therapeutic strategy for preventing the mitochondrial fission and dysfunction which occurs in the diabetic heart, thereby preventing the cardiac dysfunction observed in diabetic cardiomyopathy. In this regard, the over-expression of OPA1 has been shown to improve mitochondrial morphology in coronary endothelial cells isolated from a diabetic heart supporting the notion that OPA1 may be a potential therapeutic target to improve cardiac dysfunction in diabetes (33,64).…”
Section: Opa1 and Cardio-metabolic Diseasementioning
confidence: 70%
“…Makino et al (33) have shown in neonatal cardiomyocytes that in the presence of high glucose, O-GlcNAcylation of OPA1 suppressed OPA1 activity resulting in mitochondrial fission. The potential implications of this for the diabetic heart are discussed in a later section.…”
Section: Other Regulators Of Opa1 Functionmentioning
confidence: 99%
See 2 more Smart Citations